Single event burnout failures caused in silicon carbide power devices by alpha particles emitted from radionuclides - Marco Pocaterra; Mauro Ciappa (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2023)
Single event burnouts (SEB) threaten the safe operation of high voltage SiC power devices in a wide range of applications. The triggering of this failure mechanism has been widely documented for the case of heavy ions and neutron interactions. In this study, it is demonstrated experimentally that destructive SEB events can be triggered in SiC and Si power devices by single alpha particles in the 5 MeV energy range, such as those emitted by radioactive isotopes. Such SEB events have been observed for blocking voltages lower than the breakdown voltage of the investigated devices. The experimental setup making use of an Am241 planar source to quantitatively observe the current pulses resulting from irradiation is described in detail. The mechanism of SEB initiation by single alpha particles has been investigated by the means of TCAD simulation.The experimental and simulation results show that alpha particles can trigger SEB in both SiC and Si power devices, with SiC devices exhibiting a graver susceptibility. In particular, the simulations demonstrate that the thermal runaway is a consequence of current filamentation in the main blocking junction of the devices, due to generation of a streamer along the ionization track produced by the impinging particle. Furthermore, it is shown that the increased susceptibility of SiC devices to destructive SEB is due to the stronger local field, thinner depleted region and higher junction capacitance than in Si, resulting in higher available energy for the destructive event. The present findings may have practical implications. Given the simplicity and economy of the procedure, alpha sources can be used as a complementary technique to nucleon irradiation for the characterization of the susceptibility of power devices to SEB. Finally, the possible impact on the triggering of SEBs by alpha emitters present as contamination near the active areas of the device should be reconsidered.